Asset Seizure of Money Laundering Crimes Arising from Corruption in the Perspective of Legal Certainty and Justice - Sahuri Lasmadi; Usman Usman; Elly Sudarti; Nys. Arfa (Universitas Negeri Semarang, 2023)
This article delves into the issue of legal systems and mechanisms for confiscating assets resulting from corruption. Currently, the mechanism for asset confiscation remains unclear, particularly concerning the procedures for asset restitution, the authorized entities responsible for taking over state assets, the eligible assets that can be confiscated to compensate for state losses, and the institutions authorized to receive, store, and manage state assets resulting from acts of corruption. As a consequence, law enforcement effectiveness has been hindered. Hence, it is essential to establish a fair and definitive regulation for the confiscation of assets related to the criminal act of money laundering arising from corruption by implementing the Asset Confiscation Bill. By implementing clear and comprehensive arrangements for managing confiscated assets, it will foster a professional, transparent, and accountable law enforcement system.